4th International Symposium on High Temperature Metallurgical Processing. - Jiang, Tao (Wiley, 2013)
The scope of the book covers: The analysis, development, and/or operation of high temperature processes that involve the beneficiation of minerals, production of metals, alloys (including ferroalloys), and ceramic materialsThe innovative methods for achieving impurity segregation and removal, by-product recovery, waste minimization, energy efficiency, and utilization of complex oresThe technical, economic, and environmental issues associated with commercial-scale high temperature processing methods Nine topics are covered in this book: Hig.
Research on Inclusions in CuCr Alloy Prepared by Thermit Reduction.
Keywords: Metallurgy -- Congresses.; elektronické knihy; electronic books